The Impact of Outlining Technique on Seventh Grade Students’ Writing - Agustina, Kharisma Prita; Widyaningsih, Titik Lina (English Education and Literature Journal (E-Jou), 2026)
Writing is one of the most challenging skills for students to master in learning English. Many students face difficulties in organizing ideas coherently, developing paragraphs, and using appropriate vocabulary and grammar. The outlining technique, which involves creating a structured plan before writing, is considered an effective strategy to help students improve their writing skills. This study aims to investigate the impact of using the outlining technique on the writing ability of seventh-grade students at SMPN 1 Pakel. This study applied a pre-experimental design with a one-group pre-test and post-test model. The participants were 32 seventh-grade students of class VII-B. The instrument used was a writing test administered as a pre-test before the treatment and a post-test after the treatment. In analyzing the data, a paired-samples t-test was conducted using SPSS to determine whether there was a significant difference between the pre-test and post-test results. The findings showed that the students’ mean score improved from 55.47 in the pre-test to 74.84 in the post-test, indicating an overall increase of 19.37 points. Furthermore, the significance value of 0.00 < 0.05 confirmed that the outlining technique had a significant effect on students’ writing performance. Based on these results, it can be concluded that the outlining technique is effective in improving the writing ability of seventh-grade students at SMPN 1 Pakel